Sport and exercise psychology - Shaw, D. (Dave), 1947-; Gorely, T. (Trish); Corban, R. (Rod) (Oxon, UK ; New York : BIOS Scientific Publishers, 2005)
"This book provides concise coverage of sport and exercise psychology at the undergraduate level, and also covers the crucial basic psychology that underpins the subject. Suitable for students in sport and exercise science, sport psychology, sport studies and sports management courses, it will also be useful for coaches and athletes who wish to gain an up-to-date understanding of the key concepts, theories and research in this area."--Jacket
Sect. A. Introduction to psychology, sport and exercise -- Sect. B. Cognition and motor behavior -- Sect. C. Motivation -- Sect. D. Moods and emotions -- Sect. E. Individual differences -- Sect. F. Interpersonal processes -- Sect. G. Group processes -- Sect. H. Psychological effects of physical activity -- Sect. I. Motivation for physical activity : descriptive approaches -- Sect. J. Theories and models of exercise behavior -- Sect. K. Consultancy in sport and exercise psychology -- Sect. L. Performance enhancement -- Sect. M. Special issues.
Includes bibliographical references (pages 275-282) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Sports -- Psychological aspects; Exercise -- Psychological aspects; SPORTS & RECREATION -- Sports Psychology; Exercise -- Psychological aspects; Sports -- Psychological aspects